Implementation of Risk Management Design in the Tourism Industry at PT XYZ, Bandung Regency, Based on ISO 31000:2018 - Sina Delphia Sukmana; Machmudin Eka Prasetya (Greenation International Journal of Economics and Accounting, 2025)
This study explores the implementation of a risk management design at PT XYZ, a private company managing tourist attractions in Bandung, based on ISO 31000:2018 standard. The research aims to identify, assess, and mitigate the risks faced by the company in its operational activities. The study employed a qualitative case study approach, gathering data through interviews and observations from key management departments at PT XYZ. The findings revealed several key risks, including operational, financial, and reputational risks, which were analyzed using a risk matrix. Effective mitigation strategies, including preventive maintenance and training programs, were recommended to enhance the company’s ability to manage risks and ensure sustainable operations. This research contributes to the body of knowledge on risk management in the tourism industry, offering practical insights for other tourism-related businesses in Indonesia.